Heterogeneity at Work: Implications of the 2012 Clinical Translational Science Award Evaluators Survey - Kane, Cathleen (2013)
The Clinical and Translational Science Award (CTSA) program is an ambitious multibillion dollar initiative sponsored by the National Institutes of Health (NIH) organized around the mission of facilitating the improved quality, efficiency, and effectiveness of translational health sciences research across the country. Although the NIH explicitly requires internal evaluation, funded CTSA institutions are given wide latitude to choose the structure and methods for evaluating their local CTSA program. The National Evaluators Survey was developed by a peer-led group of local CTSA evaluators as a voluntary effort to understand emerging differences and commonalities in evaluation teams and techniques across the 61 CTSA institutions funded nationwide. This article presents the results of the 2012 National Evaluators Survey, finding significant heterogeneity in evaluation staffing, organization, and methods across the 58 CTSAs institutions responding. The variety reflected in these findings represents both a liability and strength. A lack of standardization may impair the ability to make use of common metrics, but variation is also a successful evolutionary response to complexity. Additionally, the peer-led approach and simple design demonstrated by the questionnaire itself has value as an example of an evaluation technique with potential for replication in other areas across the CTSA institutions or any large-scale investment where multiple related teams across a wide geographic area are given the latitude to develop specialized approaches to fulfilling a common mission.